2006
DOI: 10.1530/rep.1.00868
|View full text |Cite
|
Sign up to set email alerts
|

Kit ligand and c-Kit are expressed during early human ovarian follicular development and their interaction is required for the survival of follicles in long-term culture

Abstract: I B Carlsson and M P E Laitinen contributed equally to this paper AbstractThe receptor tyrosine c-Kit and its cognate ligand, c-Kit ligand (KL, stem cell factor, SCF), are involved in ovarian follicular development in several animal species. We studied the expression of KL and c-Kit using in situ hybridization and immunohistochemistry in donated human ovarian cortical tissue. The KL transcripts were expressed in granulosa cells of primary follicles, whereas the expression of c-Kit was confined to the oocyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 47 publications
9
44
0
3
Order By: Relevance
“…It was unclear whether KL supported oocyte viability during in vitro treatment or in the subsequent xenografting in this experiment. Similar results have been reported by Carlsson et al [26], who employed organ culture for human ovarian tissues. They showed that KL does not affect follicular development, although the number of viable follicles is increased.…”
Section: Kl 3 Dayssupporting
confidence: 90%
“…It was unclear whether KL supported oocyte viability during in vitro treatment or in the subsequent xenografting in this experiment. Similar results have been reported by Carlsson et al [26], who employed organ culture for human ovarian tissues. They showed that KL does not affect follicular development, although the number of viable follicles is increased.…”
Section: Kl 3 Dayssupporting
confidence: 90%
“…In mice, KL inhibited the apoptosis of oocytes from primordial follicles after in vitro culture [Jin et al, 2005] through an increase in the expression of antiapoptotic proteins Bcl-2 and Bcl-xL and a reduction in the expression of proapoptotic factor Bax. Other authors have also demonstrated that inhibition of the KL/c-kit interaction increases the proportion of atretic follicles at days 7 and 14 of culture in humans [Carlsson et al, 2006] and promotes oocyte death in mice Doneda et al, 2002;. In our study, KL addition until day 8 of culture was important for maintaining follicle and oocyte growth regardless of the substance tested from day 8 to day 16 of culture.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, in goat preantral follicles, different concentrations of KL (1, 10, 50, 100, or 200 ng/ ml) promoted follicular activation as early as after 1 day of in vitro culture [Celestino et al, 2010]. Nevertheless, in humans KL did not have an effect on preantral follicle development after 7 days of culture [Carlsson et al, 2006], indicating that the roles of KL differ between species. In the present study, after 8 days of culture the presence of KL in vitro as well as its replacement by FSH+KL or FSH alone maintained (KL/KL and KL/FSH+KL) or significantly increased (KL/FSH) the percentage of follicular activation until day 16.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that KIT-KL might not be associated with the activation of porcine primordial oocytes, although they are necessary for the survival of the oocytes. Similar results have been reported by Carlsson et al [38], who employed organ culture for human ovarian tissues. They showed that KL did not affect follicular development, although the number of viable follicles was increased.…”
Section: Stimulatory Factors Of Primordial Oocytessupporting
confidence: 90%